2018
DOI: 10.1111/ijn.12621
|View full text |Cite
|
Sign up to set email alerts
|

Expectations and experiences of patients with osteoarthritis undergoing total joint arthroplasty: An integrative review

Abstract: This review is the first to capture the osteoarthritic patients' educational needs from their perspectives. The biopsychosocial model can address the multidimensionality (biological, psychological, and social) of patients' educational needs. A robust infrastructure supporting interprofessional collaborative practice and continuity of care should be adopted to enhance current educational efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…A team of surgeons, physiotherapists and registered nurses should continuously provide the patient with information about common postsurgical recovery time and symptoms. This approach is in alignment with a recent review that suggested continuous information and education is essential for patients to be able to cope with pain and to understand their symptoms (See, Kowitlawakul, Tan, & Liaw, 2018).…”
Section: Discussionmentioning
confidence: 79%
“…A team of surgeons, physiotherapists and registered nurses should continuously provide the patient with information about common postsurgical recovery time and symptoms. This approach is in alignment with a recent review that suggested continuous information and education is essential for patients to be able to cope with pain and to understand their symptoms (See, Kowitlawakul, Tan, & Liaw, 2018).…”
Section: Discussionmentioning
confidence: 79%
“…This limits the interactions between nurses and patients and can result in some patients being provided generic information while others received none (Friberg, Granum, & Bergh, 2012; Winsett, Rottet, Schmitt, Wathen, & Wilson, 2016). Previous studies concurred the inadequate support in meeting patients’ informational, psychosocial and emotional needs even after their surgery (Jones et al, 2015; See, Kowitlawakul, Tan, & Liaw, 2018). On this matter, Seeman (2019) cautioned that any failure to provide the desirable patient education can result in repercussions such as postoperative complications and hospital readmissions of patients with poor surgical outcomes.…”
Section: Introductionmentioning
confidence: 83%
“…Previous studies concurred the inadequate support in meeting patients' informational, psychosocial and emotional needs even after their surgery (Jones et al, 2015;See, Kowitlawakul, Tan, & Liaw, 2018). On this matter, Seeman (2019)…”
Section: Backg Rou N Dmentioning
confidence: 90%
“…Moreover, previous experience of care and preferences can also influence outcomes. 106 According to a recent systematic review, the likelihood of nocebo effects is increased when previous negative knowledge or expectations exist. In addition, pre-existing psychological traits (eg, anxiety) may exacerbate the nocebo effect.…”
Section: Subjective Nursing Outcomes Can Be Modulated By Contextuamentioning
confidence: 99%